Pengaruh Kemudahan Penggunaan dan Promosi terhadap Keputusan Pembelian di Marketplace Shopee - Venika Salsabila Ayu Pramarini; Sumaryanto Sumaryanto; Lamidi Lamidi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The aim of this research is to analyze t effect of ease of use and promotion on purchasing decisions in the shopee marketplace. The population of this study were Shopee users in Solo. The sample in this study were 100 Shopee users in Solo. The method used in sampling was purposive sampling method. The results of the analysis state that all statements regarding ease of use, promotion and purchasing decisions are declared valid because the p-value <0.05 and reliable because because Cronbach's alpha> 0.60. The results of the classical assumption test show that all variables have passed the multicollinearity, autocorrelation, heteroscedasticity, and normality tests with normal distribution. The results of linear regression analysis obtained the equation Y = 3.429 + 0.310 X₁ + 0.619 X₂. The t test results show that ease of use has no significant effect on purchasing decisions in the Shopee marketplace , while promotion has a significant effect on purchasing decisions in the Shopee marketplace . The F test results showed that the regression model used in this study was correct. The results of the R² test show that the magnitude of the contribution of the influence of the independent variable on the dependent is 52.9%, the remaining 47.1% is influenced by other factors outside the variables studied.